FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN KINERJA PERUSAHAAN SEBAGAI VARIABEL MEDIASI - Eugenia Steviana; Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to obtain empirical evidence regarding family ownership, independent commissioner, audit committee, and foreign ownership of firm value with firm performance as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange. The observation period in the study was 2017-2019. Samples taken in this study 135 data using non-probability sampling with purposive sampling technique and data analysis techniques using the Partial Least Square method with the SmartPLS 3.3.2 application. The results of this study indicate that family ownership, independent commissioner, audit committee, and foreign ownership have a negative and insignificant direct effect on firm value. This study provides evidence that firm performance can mediate the effect of the independent commissioner on firm value. However, it cannot mediate the influence of family ownership, audit committees, and foreign ownership.